2017
DOI: 10.1111/cas.13177
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐155‐5p promotes hepatocellular carcinoma progression by suppressing PTEN through the PI3K/Akt pathway

Abstract: MicroRNA‐155‐5p (miR‐155‐5p) has been reported to play an oncogenic role in different human malignancies; however, its role in hepatocellular carcinoma (HCC) progression is not clearly understood. In this study, we used real‐time PCR in 20 rats with chemically‐induced HCC, 28 human HCC tissues, and the matched paracarcinoma tissues, and HCC cell lines to determine the expression patterns of miR‐155‐5p and PTEN mRNA. Algorithm‐based and experimental strategies, such as dual luciferase gene reporter assays, real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 32 publications
2
106
0
Order By: Relevance
“…These factors are related to certain cellular biological processes, such as cell proliferation, migration, apoptosis, and angiogenesis. For example, PTEN is well known as a key factor in the PI3 K/Akt signaling and acts as a suppessor gene of hepatocellular carcinoma . To our surprise, La and La‐related protein are closely connected to liver cancer .…”
Section: Discussionmentioning
confidence: 89%
“…These factors are related to certain cellular biological processes, such as cell proliferation, migration, apoptosis, and angiogenesis. For example, PTEN is well known as a key factor in the PI3 K/Akt signaling and acts as a suppessor gene of hepatocellular carcinoma . To our surprise, La and La‐related protein are closely connected to liver cancer .…”
Section: Discussionmentioning
confidence: 89%
“…22,25 As shown in Figure 4A,B, we found that overexpression of miR-623 did not affect the total level of Akt and mammalian target of rapamycin (mTOR), whereas phosphorylated form p-Akt and p-mTOR was significantly inhibited in HCC cells. * P < .05 compared with negative control (NC).…”
Section: F I G U R E 3 Upregulation Of Mir-623 Induces Apoptosis Of Hmentioning
confidence: 88%
“…[22][23][24][25] Inhibiting these signaling pathways is considered to be an effective method for cancer therapy. [22][23][24][25] Inhibiting these signaling pathways is considered to be an effective method for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…AKT is a key regulatory factor of cell proliferation (21). In the present study, the expression of AKT was knocked down in a HaCaT cell model via siRNA silencing.…”
Section: The Function Of Akt In Hacat Cell Proliferation and Mitosismentioning
confidence: 88%